Neurophysiology of Grasping Actions: Evidence from ERPs - Koester, Dirk; Schack, Thomas; Westerholz, Jan (Frontiers in Psychology, 2016)
We use our hands very frequently to interact with our environment. Neuropsychology together with lesion models and intracranial recordings and imaging work yielded important insights into the functional neuroanatomical correlates of grasping, one important function of our hands, pointing towards a functional parietofrontal brain network. Event-related potentials (ERPs) register directly electrical brain activity and are endowed with high temporal resolution but have long been assumed to be susceptible to movement artefacts. Recent work has shown that reliable ERPs can be obtained during movement execution. Here, we review the available ERP work on (uni) manual grasping actions. We discuss various ERP components and how they may be related to functional components of grasping according to traditional distinctions of manual actions such as planning and control phases. The ERP results are largely in line with the assumption of a parietofrontal network. But other questions remain, in particular, regarding the temporal succession of frontal and parietal ERP effects. With the low number of ERP studies on grasping, not all ERP effects appear to be coherent with one another.. Understanding the control of our hands may help to develop further neurocognitive theories of grasping and to make progress in prosthetics, rehabilitation or development of technical systems for support of human actions.